2D petroleum system analysis of the Tarfaya Basin, on-offshore Morocco, North Africa. (November 2016) - Sachse, Victoria F.; Wenke, Axel; Littke, Ralf; Jabour, Haddou; Kluth, Oliver; Zühlke, Rainer
Abstract: This study presents a 2D basin model along a transect crossing the on- and offshore Tarfaya Basin, Morocco, in SE-NW direction. The aim of the project is to investigate the thermal evolution of the basin fill and its influence on the petroleum system. The modelling is based on a recently interpreted seismic section and includes new and published geochemical and organic petrological data from five wells. Core samples and cuttings provide information, which was used for thermal calibration of the model. Vitrinite reflectance in the Jurassic offshore basin fill reaches more than 1%. The modelled subsidence history, in combination with kinetic and geochemical data, were used to model hydrocarbon generation. In order to investigate the temperature, hydrocarbon generation and its timing, two 1D geohistory curves were extracted, one for the onshore inner shelf and one for the offshore deep water area. The modelling results suggest that deepest burial in the modern offshore area occurs at present day, whilst deepest burial in the onshore area occurred during the Oligocene depending on the location on the inner shelf. Based on the burial- and thermal evolution, significant hydrocarbon generation from Lower Jurassic source rocks took place from the Early Cretaceous until the Neogene in the offshore area. In the onshore area, petroleum generation ceased in the Late Cretaceous. As salt deposition may play an important role in the thermal history in the Tarfaya Basin, a second model including salt was built, indicating increased Early Cretaceous hydrocarbon generation in the offshore area. Highlights: 2D basin/petroleum system modelling of a transect crossing on-offshore Tarfaya Basin, Morocco. Maturity, temperature and burial history plots for three key locations (deep offshore, slope and onshore). Testing impact of salt plumes on temperature and maturity development. Implementation of geochemical data for the on-offshore area. Compilation of source rock data.